2020
DOI: 10.1002/er.5638
|View full text |Cite
|
Sign up to set email alerts
|

The significance of anti‐fluorite Cs 2 NbI 6 via its structural, electronic, magnetic, optical and thermoelectric properties

Abstract: The structural, electronic, magnetic, optical and thermoelectric properties of anti-fluorite Cs 2 NbI 6 were investigated using full potential augmented plane wave method of density functional theory. Structurally, Cs 2 NbI 6 was found to be cubic in ground state from values of tolerance factor (1.04) and formation energy (−22.3 eV). While, it's ferromagnetic nature was predicted from volume optimization process. In spin down channel, the compound was explored as indirect band gap (E g(Γ-X) = 1.97 eV) semicond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…This code is obtained from CBT theory which is further used to calculate transport coefficient σ αβ (ε) of electrical conductivity. 42,43 The mathematical expression is given below: In the above equations, N, υβ (i, k), K and τ are the number of k-points, group velocity, wave vector and relaxation time, respectively. Integration of the transport coefficient gives other factors upon which thermoelectric response depends Here α, Ω, ƒ 0 , μ and β are tensor vector, unit cell volume, Fermi Dirac distribution, carrier concentration and charge on electron, respectively.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…This code is obtained from CBT theory which is further used to calculate transport coefficient σ αβ (ε) of electrical conductivity. 42,43 The mathematical expression is given below: In the above equations, N, υβ (i, k), K and τ are the number of k-points, group velocity, wave vector and relaxation time, respectively. Integration of the transport coefficient gives other factors upon which thermoelectric response depends Here α, Ω, ƒ 0 , μ and β are tensor vector, unit cell volume, Fermi Dirac distribution, carrier concentration and charge on electron, respectively.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…A number of researchers carried investigations on materials in A 2 BX 6 group and reported them as excellent absorber to be used in solar cell applications. [4][5][6][7][8][9][10][11][12] Also materials of this group have been reported with excellent thermoelectric properties. [4][5][6][7] Among A 2 BX 6 defective perovskites, Rb/Cs 2 TeI 6 compounds have not been studies at experimental or theoretical level for solar cells and thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Also materials of this group have been reported with excellent thermoelectric properties. [4][5][6][7] Among A 2 BX 6 defective perovskites, Rb/Cs 2 TeI 6 compounds have not been studies at experimental or theoretical level for solar cells and thermoelectric applications. Abriel 13 prepared Rb 2 TeI 6 and reported it with cubic A 2 BX 6 at 340 K. Sidey et al 14 reported lattice constant of Cs 2 TeI 6 as 11.700 Å from his experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vacancy ordered double perovskites, were widely studied as alternative of lead perovskites. As result, compounds of this class were proven as good conductors and have been considered as solar cell absorbers [14][15][16][17][18][19].This group of compounds is generally represented by A2BX6, where, A, B are cations, and X is a halide [20]. The structure of A2BX6 compounds has close similarity to the structure of cubic perovskite ABX3 with half of the B sites cation removed in an organized method.…”
Section: Introductionmentioning
confidence: 99%